Scoring system for papillary thyroid carcinoma - a histopathological study - Dr. Swathi C. Prabhu; Dr. Umashankar T. (Tropical Journal of Pathology and Microbiology, 2018)
Background: Cancer of the thyroid gland is the most common endocrine malignant neoplasm, and papillary thyroid carcinoma (PTC) accounts for majority of the cases. PTC cases are identified by its distinct histopathological features. Due to lack of definable criteria and overlapping features seen in other diseases of thyroid giving rise to false positive cases and errors in diagnosis may reflect drastically on the prognosis and treatment outcome. Objective: To analyse the frequency of PTC microscopic criteria in a series of benign lesions of thyroid and PTC cases and to build an optimal cut off score which could help us differentiate between these cases. Materials and Methods: The study included 86 thyroid lesions, 43 benign and 43 PTC cases. Histopathological parameters analysed included colloid, papillae, nuclear crowding, nuclear grooving, nuclear enlargement, oval nucleus, nuclear clearing. Results: The above mentioned parameters could differentiate between benign and PTC cases. Based on sensitivity and specificity, the cut off derived for every parameter is as follows: colloid <50%, papillae >1%, nuclear crowding >25%, nuclear grooving >5%, nuclear enlargement >50%, ovoid nucleus >25%, nuclear clearing>50%. The scoring system was built based on these parameters. The score proposed helped us to classify benign and PTC cases. PTC cases scored a total score of >7 indicating that seven can be considered as cut off value to differentiate between benign and PTC cases. Conclusion: Definite distinction between benign and PTC cases was possible when all the parameters were clubbed together with an important role in cases with diagnostic dilemma.